A Preliminary Study on Characterizing Syntactic Processing and Pause Patterns in Bilingual English-Bahasa Indonesia Specific Language Impairment - Anjarningsih, Harwintha Y.; Huda, Nurul; Kirana, Angkita Wasito (OKARA: Jurnal Bahasa dan Sastra, 2024)
A 12-year-old boy received a diagnosis of an unspecified "language disorder," suggesting the possibility of Specific Language Impairment (SLI) along with atypical pausing behavior. Interested to find out the possibility of incorporating pausing behavior into SLI diagnosis, this research sought to explore the distinctions in pause patterns between the spoken Bahasa Indonesia (BI) and English of Indonesian children, utilizing data from the child with suspected SLI (sSLI) and a control group for comparative analysis. Employing a quantitative approach and analyses related to phonology, syntax, and bilingual language production, the study revealed that the child with sSLI tended to display longer and more frequent pauses than the control group, particularly during communication in BI. Despite multiple influencing factors, pause patterns had the potential to serve as an indicative tool and a means to integrate bilingualism into the diagnosis of SLI.